ІНТЕГРАТИВНЕ УЗАГАЛЬНЕННЯ ФОРМ ІНТЕРАКТИВНИХ МЕТОДІВ НАВЧАННЯ (Педагогіка вищої та середньої школи, 2007)
This article considers from and content interactively method theaching of repairing future teachers. The author of the analyses the condition effect interactively method studies.